Effect of some agrochemicals on the growth and sporulation of the fungus Metarhizium anisopliae - ATEHORTÚA-C., MARTA MARÍA; LONDONO-Z., MARTHA EUGENIA (Revista Colombiana de Entomología, 1994)
The fungus Metarhizium anisopliae has been found attacking white grubs (Coleoptera: Scarabaeidae) under natural conditions in Antioquia, Colombia. This fungus has a great potential as biological control of the white grubs because it attacks all the developmental stages of the insect. Its easy multiplication on rice allows its production at the farm level. However, it’s survivorship capacity when it has to compete with the most common agrochemicals used in the region is unknown. For this reason, an experiment was carried out in order to evaluate the effect that over the growth and sporulation of the fungus M. anisopliae have some fungicides (dentin hydroxide, cymoxanilmancozeb), insecticides (chlorpyrifos, diazinon), herbicide (Round-up), and fertilizers (manure, urea, 10-30-10, CaCO3), using three different concentrations of each product (50, 5, and 0.5 ppm). The treatments were applied at the culture medium (SDA) in Petri dishes. The fungus was sowed in the center of each petri dish, and the growth was annotated. In this experiment a randomized complete block design was used, with 28 treatments and 3 replications. Chlorpyrifos and dentin hydroxide inhibited the fungus growth 9, 15, and 18 days after sowing, with a concentration of 50 ppm. Sporulation days fluctuated between 6 and 8, being the highest for cymoxanil-mancozeb and clorpirifos, because this completely avoided fungus sporulation, even until 36 days after sowing in SDA.